Munke og nonner på danske kirkevægge: Nogle refleksioner over karmelitermunkene i Sæby Kirke - Jørgensen, Kaare Rübner (Hikuin, 2007)
Monks and Nuns on Danish Church Walls Some Reflections on the Carmelite Monks in Sæby Church By Kaare Rübner Jørgensen In the still existing medieval churches of Denmark murals of monks and nuns are very rare. Therefore, the former Carmelite church of Sæby in Northern Jutland with its twenty-four friars is unique. As some of the paintings and many of the ribbons, which once identified the depicted Carmelites, are rather mutilated, visitors are no longer able to identify more than fourteen of the twenty-four friars. However, a book, written by a German abbot John Trithemius in 1492, contained a catalogue of 75 outstanding Carmelites. As this catalogue can be shown to have been the source of the ribbons, it is possible not only to fill the textual gaps, but also to identify twenty-tree of the twenty-four friars. These friars, praised for their wisdom and skill in Theology, belonged to the thirteenth and fourteenth centuries and have been dead in hundred or more years, when the paintings were made on the vaults of the church (1512-1523). Their wisdom was therefore neither new nor modern, but represented a traditional scholastic learning. At the time of the painting, however, the East-Danish Carmelites, especially those living in the friary of Elsinore or studying at the University of Copenhagen, became strongly influenced by Erasmus of Rotterdam and his Biblical Humanism. The author therefore proposes that the murals in Sæby should be seen as a reaction to this modern tendency in Theology. If such an interpretation is acceptable, the painting of the friars in the church of Sæby is evidence of a hitherto unknown controversy among the Danish Carmelites on the Eve of the Reformation. Consequently, the murals thus get a quite new significance.